Right to information one should know - Edited by Garg, Ajay Kumar (Delhi Nabhi Publications, 2023)
The book incorporates Text of Right to Information Act 2005 Text of Right to Information Rules 2012 Text of RTI (Term of Office Salaries Allowances etc. of Information Commissioners) Rules 2019 Text of Various State Rules and Important Circulars/Decisions of CIC.
Keywords: Right to Information Act; Right to Information Rules